Review of “Initial English Language Teacher Education : International Perspective on Research, Curriculum and Practice” - Soubakeavathi, Rethinasamy (National University of Singapore (NUS), 2018)
This book is aimed at providing an understanding of the processes and experiences that teacher educators and teacher students undergo in their early stages of the English language teacher education journey, with a focus on the voices of teacher educators and teacher learners. The book also aims to encourage institutions to move from training to development in the quest for sustainability and vision in teacher education. The book delivers the intended aims by providing research based studies conducted in teacher education settings in various countries, namely, Argentina, Brazil, China, Colombia, Kenya, Singapore, South Africa, Spain, United Kingdom and Uruguay.